The Spirit of St. Louis: A Conference Report - Gwil Evans (Journal of Applied Communications, 1985)
For three days in mid-February 1985, seventy-some participants met in St. Louis for a national conference called "International Agricultural Programs and Agricultural Communications - Partners for International Development," sponsored by the Association of U.S. University Directors of International Agricultural Programs and ACE. This report looks from the communicator's perspective at the character and outcomes of that meeting.